Drug Therapy of Cognitive Dysfunction in Minimally Invasive Surgery during Anesthesia with Sevoflurane - M. I. Neymark; V. V. Shmelev; A. A. Rakhmonov; E. A. Nazarchuk (Вестник анестезиологии и реаниматологии, 2022)
The objective: To conduct a comparative assessment of efficacy of Cytoflavin and Cellex for management of cognitive disorders after videolaparoscopic cholecystectomy performed under general inhalation anesthesia with sevoflurane.Results. In three representative groups (n = 30) of patients, markers of inflammation (CRP and IL-6), levels of brain-specific proteins (S-100 and NSE) were studied. Neuropsychological testing were performed by using the MoCA test, frontal dysfunction test battery (FAB) by two stages (stage I ‒ on the eve of the operation, stage II ‒ on the 7th day of the postoperative period). In patients of Group I (n = 30), disorders of higher mental functions of the early postoperative period persisted, which served as the basis for finding ways to eliminate and manage the identified disorders. For this purpose, Cytoflavin was used in Group II (n = 30), and Cellex was used in Group III (n = 30).Comparative characteristics of the level of brain-specific proteins revealed a statistically significant decrease at stage I in Groups II and III versus Group I. The lowest level of both NSE (by 1.45 μg/l, p = 0.041) and S-100 (by 10.1 ng/l, p = 0.044) was observed in Group III versus Group II. In addition, at the second stage of the study, the greatest severity of the inflammatory response was noted in Groups II and III of patients compared to Group I and this degree of severity could be potentiated by the ongoing drug therapy. If in Group I, disorders of higher mental functions persisted on the 7th day of the postoperative period, then as a result of the ongoing drug therapy in Groups II and III, it was possible to achieve significantly better results of neuropsychological testing.Conclusion. Administration of drug therapy contributed to the improvement of higher mental function eliminating cognitive deficit in the early postoperative period.